# Living/minimum wage: Influential citizen talk in twitter. (September 2016) - Lorenzo-Dus, Nuria; Di Cristofaro, Matteo
Abstract: There has been a major cultural shift away from ׳passive׳consumption to more active production of digital texts by citizens. Yet, this does not mean that we all participate in digital media in the same ways and for the same reasons. Nor does it mean that we all have the same level of access to digital networks. This article seeks to contribute to a better understanding of the diversity and fluidity of citizen participation in digital environments by examining the discourse style of a particular group of digital users, namely citizens whose contributions become crowdsourced to prominence in microblogging. We refer to this form of citizen participation as ׳influential׳, in as much as the discourse of these citizens attracts inordinate levels of attention and can trigger social contagion. We conduct a Corpus-Assisted Discourse Study of a corpus of tweets posted by a group of citizens who emerge as ׳influential׳ within a Twitter debate about the minimum/living wage. Our analysis reveals that their discourse style is characterised by (i) limited content originality but a high participation rate; (ii) a continuum of thematic engagement; (iii) high levels of emotionality; and (iv) a preference towards stance-taking acts that convey full confidence in one׳s views.